Tumors With Intrahepatic Bile Duct Differentiation in Cirrhosis. Issue 1 (January 2015) - Facciuto, Marcelo E.; Singh, Manoj K.; Lubezky, Nir; Selim, Motaz A.; Robinson, Dorothy; Kim-Schluger, Leona; Florman, Sander; Ward, Stephen C.; Thung, Swan N.; Fiel, MariaIsabel; Schiano, Thomas D.
<x xml:space="preserve">Abstract</x> Background The role of liver transplantation (LT) in the management of cirrhotic patients with tumors exhibiting intrahepatic bile duct differentiation remains controversial. The objective of this study was to characterize the spectrum of these tumors and analyze post-LT outcomes. Methods Retrospective pathology database search of explant histology analysis of liver transplants between April 1993 and November 2013. Results Thirty-two patients were analyzed, 75% were men with a mean age of 60 years. Seven patients had nodules demonstrating intrahepatic cholangiocarcinoma (I-CCA), nine had I-CCA nodules occurring concomitantly with hepatocellular carcinoma (HCC), and 16 had mixed HCC-CCA nodules. The median number of tumors was 1 and size was 2.5 cm. Overall patient survival post-LT at 1 and 5 years was 71% and 57%, respectively. Patients within Milan criteria, especially with I-CCA features, showed a 5-year tumor recurrence rate (10%) and 5-year survival rate (78%) comparable with other patients having HCC within Milan criteria. Conclusion This series showed that patients with CCA within Milan criteria may be able to achieve acceptable long-term post-LT survival.